ICT-Pedagogy Integration in Elementary Classrooms: Unpacking the Pre-service Teachers’ TPACK - MARK GILL M. MERCADO; FLORANTE P IBARRA (Indonesian Research Journal in Education |IRJE|, 2019)
This study aimed to investigate the Technological Pedagogical Content Knowledge (TPACK) self-efficacy and ICT integration skills of elementary pre-service teachers in elementary classrooms. The respondents were fifty-two (52) elementary pre-service teachers enrolled in the student teaching program at the Central Luzon State University. Results revealed that most of respondents perceived themselves to be highly proficient in all domains of TPACK framework: Technology Knowledge (TK), Content Knowledge (CK), Pedagogical Knowledge (PK), Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK) and Technological Pedagogical Content Knowledge (TPCK). Most of them were found to be good in integrating ICT in classroom instruction, particularly in terms of planning and implementation.Respondents’ GPA in Educational Technology and ICT-related courses was found to have negative significant relationship with their planning and implementation of ICT-Integrated instruction. Their TPACK self-efficacy had a highly significant relationship with their planning and implementation of ICT-integrated instruction.